Implementation of Legal Protection for Victims Regarding Domestic Violence According to Law Number 23 of 2004 in Bandung City - Indra Saputra; Legia Luthfi Fauziyah; Lutfi Shidqi Rohmatulloh (Jurnal Restorasi : Hukum dan Politik, 2024)
Domestic abuse is a crime in Indonesia that carries the danger of criminal law. It causes physical and emotional pain and suffering to the victim. Examining the potential impact of domestic violence prevention legislation on law enforcement was the driving motivation behind this research. This study employs the descriptive technique. To shed light on occurrences that have occurred in the past or are happening today, researchers often turn to descriptive study.The findings demonstrated that eradicating domestic violence may start with the elimination of its causes and triggers. Regarding this matter, there are several approaches and initiatives that may be used to either eliminate or significantly lessen the impact of domestic violence.